Long-term trends and future projections of larynx cancer burden in China: a comprehensive analysis from 1990 to 2030 using GBD data - Bijuan Chen; Zhouwei Zhan; Weining Fang; Yahan Zheng; Sisi Yu; Jiali Huang; Jianji Pan; Shaojun Lin; Qiaojuan Guo; Yun Xu (Scientific Reports)
Abstract Larynx cancer poses a significant public health challenge in China, with rising incidence and mortality rates over the past decades. Understanding the long-term trends and underlying factors is crucial for effective intervention and policy formulation. Data were utilized from the global burden of disease (GBD) Study 2021 to analyze the incidence, prevalence, mortality, disability-adjusted life years (DALYs), years lived with disability (YLDs), and years of life lost (YLLs) due to larynx cancer in China from 1990 to 2021. Joinpoint regression analysis identified key changes in trends, while age-period-cohort (APC) analysis and decomposition analysis quantified the contributions of aging, epidemiological changes, and population growth to these trends. Our study found a significant increase in the incidence and prevalence of larynx cancer in China, particularly among males. The age-standardized incidence rate (ASIR) and age-standardized mortality rate (ASMR) for males were substantially higher than those for females. Decomposition analysis revealed that aging was the primary driver of increasing incidence and mortality rates, while epidemiological changes had a mitigating effect. Joinpoint analysis identified periods of rapid urbanization and economic growth as key turning points for increased incidence. Bayesian APC models projected a continued upward trend in incidence rates up to 2030. The rising burden of larynx cancer in China underscores the need for targeted public health interventions, including smoking cessation programs, environmental pollution control, and early detection strategies. Addressing gender disparities and implementing effective prevention measures are crucial to mitigating the impact of larynx cancer in China.